2008
DOI: 10.1038/ijir.2008.16
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and pathophysiology of male sexual dysfunction

Abstract: Male sexual dysfunction (MSD) is a common disorder associated with a wide range of physical and psychological conditions. Erectile dysfunction, the most commonly studied aspect of MSD, is common and increases with age and with certain comorbid conditions. The pathophysiology of ED and other forms of MSD can be traced to a variety of etiologies, including vascular, hormonal, psychiatric, iatrogenic and potentially neurobiological causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…In particular, beside organic disorders, many different drugs can cause ED by affecting sexual hormone levels, neurotransmission, or blood circulation. Among them, antidepressants (especially those acting on the serotoninergic pathways), neuroleptics, and antihypertensives are the drugs most often associated to SD, including ED [25].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, beside organic disorders, many different drugs can cause ED by affecting sexual hormone levels, neurotransmission, or blood circulation. Among them, antidepressants (especially those acting on the serotoninergic pathways), neuroleptics, and antihypertensives are the drugs most often associated to SD, including ED [25].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, ED could be attributed to any combination of hormonal deficiency, arterial insufficiency, neurological impairment, adverse reaction to drugs, systemic chronic disease, psychological disturbance, or cavernosal defects [47]. However, a recent hemodynamic study of fresh human cadavers indicated that a rigid erection was unequivocally attainable after erection-related veins were removed in all subjects – despite the fact that their sinusoidal tissues were dead [48].…”
Section: Pathophysiology Of Erectile Dysfunctionmentioning
confidence: 99%
“…Until the 1980s, the treatment options were limited to psychosexual therapy and placement of penile implants, and through that time it was believed that ED was primarily due to psychogenic causes. With the introduction of prostaglandin intracavernosal injections in the late 1980s, the vasculogenic etiologies of ED became better understood, and the connection between late onset hypogonadism and ED led to research elucidating the hormonal etiologies of the condition (Kaminetsky 2008). Finally, the new oral treatment with PDE5 inhibitors has led to the current understanding of the pathophysiology of ED as well as the physiology of erection.…”
Section: Erectile Dysfunctionmentioning
confidence: 99%